A participação de escolas da rede escolar pública municipal de Santa Maria (RS) no Sistema de Avaliação da Educação Básica - Duarte, Adriene Bolzan (2014)
This paper reports on research undertaken as part of the Post-Graduate Education (PPGE / CE / UFSM) Education Center of the Federal University of Santa Maria, as part of the investigative actions of a Research Network "Educational Innovations and Public policy Evaluation and Improvement of Education in Brazil ", linked to the group of Studies, Research and Interventions" Innovation in Education, Educational Practices and Teacher Education "Teaching and Research group, School & Teacher Training. With it we aim to understand the repercussions of Evaluation System of Basic Education in the organization and development of school work. For this we propose to answer the following research problem: How the participation of schools in the actions of the Basic Education Evaluation System involves the organization and development of school work? In order to operationalize research actions, formulated from the central issue, more specific investigative questions: (1) How is the process of organization and implementation of Proof and Evidence Saeb Brazil? (2) that the coordinators have perceptions about the participation of the Evaluation System of Basic Education process? (3) How does the organization of the school to participate in the Assessment System of Basic Education?. Used as the main theoretical and conceptual and methodological contribution and practical (1) ideas about educational policy Saviani (2008) and Altmann (2002), (2) studies on policy evaluation Freitas (2007) and Ravitch (2011); (3) work concept proposed by Souza-e-Silva (2004); (3) the concept of democratic management and school autonomy for Paro (2001); to treat school as the context of school work we approach the propositions of Di Giorigi (2004), Rockwell (1995) and Thuler (2001). Thus, we developed a qualitative research nature, Municipal Public Schools in Santa Maria / RS, with which we interact strongly in the years 2012 and 2013. Sources of information for our research are subject coordinators from schools of basic education and engineers Polo Application of Evidence and Proof Saeb Brazil. The instruments for data collection were interviews. With the Roadmap Interview I interviewed 27 coordinators of municipal public elementary schools in Santa Maria / RS and the Interview Guide II interviewed 9 of these coordinators. With the Interview Guide III interviewed two coordinators Polo Application of Evidence and Proof Saeb Brazil. From the analysis of the information collected organize the results into 8 parts, namely: 1) the organization of the process of implementation of Proof and Evidence Saeb Brazil; 2) Development of Evidence and Proof Saeb Brazil; 3) Method of application of Evidence and Proof Saeb Brazil; 4) Difficulties encountered in the application of Evidence and Proof Saeb Brazil; 5) Agree or disagree with the outcome of the last IDEB schools; 6) Aspects taken into consideration in the evaluation of basic education; 7) Performing actions about IDEB 2011 and 8) Actions taken in the preparation of school to join Saeb 2013. Accordingly we were allowed to answer each of the research questions separately. In answering the research objective list of the main repercussions of Saeb the organization and development of school work, they are (1) Result Saeb provides ranking; (2) Lack of assessment tools to evaluate the Saeb school work; (3) Lack of Saeb Policy on school organization; (4) Strong distancing School Saeb and (5) Performing actions of decontextualized school needs. We conclude that the impact of Saeb look in the forms of organization and development of school work allows us to say that the way you have organized, implemented and interpreted Saeb currently makes having a negative impact on school organization. The ways of using Saeb has represented public school kicker, kicker education and jeopardizes the organization and the development of democratic self schoolwork.